(untitled) (American & British Studies Annual, 2013)
In the chapter on new comic voices in modern British drama, Christopher Innes noted that Patrick Marber’s play Dealer’s Choice (1995) “follows Mamet’s American Buffalo or Glen Garry Glen Ross in focusing on an all-male society where dealings, whether in business or cards, become a vicious test of manhood.” In Dealer’s Choice, the border between reality and game is blurred; poker dominates the lives and everyday discourse of Marber’s protagonists. Perhaps not accidentally, the play begins and ends with the toss of a coin. Despite the presence of comic elements, the play conveys a pessimistic view of society, dominated by self-deception and fraudulent schemes. This article aims to examine the production of Patrick Marber’s Dealer’s Choice by the Dejvice Theatre at the International Festival Theatre in Pilsen in 2011. The play explores a parallel between life and poker in terms of expectation, experience, and memory embedded in a given space and projected onto people and events. It is argued in this article that a particular social space gives rise to various types of identity through interrelationships and social patterns. Moreover, this paper focuses on the personalities of particular protagonists, their motivation to play, and how their relationships are developed and destroyed by poker, or rather, by their poker addiction.